Aligning Research and the Current Practice of Performance Management. Issue 2 (4th July 2016) - Ledford, Gerald E.; Benson, George; Lawler, Edward E.
Abstract : The debate over eliminating performance ratings addresses many important theoretical and practical issues. However, the academic debate on the topic is disconnected from the concerns of practitioners. Knowledge gained from theory-driven research is not leading practice on the use of performance ratings, despite the large volume of potentially relevant research findings. Many organizations are charging ahead with performance management solutions that seem sensible to them. They may be interested in academic research, but they are not waiting for it. We will argue that academic researchers who hope to influence practice need to better understand the concerns of practitioners and the research opportunities that are presented by contemporary practice.